Internet self-efficacy, computer self-efficacy and cultural factors on knowledge sharing behavior - Teh, Pei Lee; Chong, Chin Wei; Yong, Chen Chen; Yew, Siew Yong (Academic Journals, 2010)
Knowledge sharing has been the focus of research within organizations, yet very few studies have been conducted on the influence of knowledge sharing self-efficacy and cultural factors on individuals' knowledge sharing behavior. Given the unique social and cultural aspects of the Chinese community, this study aimed to examine the relationship between the internet self-efficacy, computer self-efficacy, cultural factors and knowledge sharing behavior among the Chinese. Data were collected from 135 Chinese students studying in Malaysian universities. This study included three variables relating to knowledge sharing self-efficacy (i.e., internet self-efficacy, beginning-level computer self-efficacy, and advanced-level computer self-efficacy) and three variables relating to cultural factors (that is, face-saving, face-gaining and guanxi). Results from the multiple regression analysis showed that advanced-level computer self-efficacy, face-gaining and guanxi were found to have significant and positive relationships with knowledge sharing behavior. Face-saving was reported to have a significant and negative relationship with knowledge sharing behavior. This research and its findings had resulted in both theoretical contribution and practical implications.